Spillover Effects of the Russia-Ukraine Conflict: Implications for the Euro-US Dollar Exchange Rate - Alsakarneh, Raad Abdelhalim Ibrahim; Abusamra, Omar Akram (Unisia, 2025)
The Russia-Ukraine conflict has garnered significant attention due to its geopolitical ramifications. By employing a pair conditional BEKK model and including multiple major exchange rates, this research aims to provide a robust assessment of the spillover effects and their significance in the context of the ongoing conflict. To accomplish this, weekly data from June 6, 2022, to July 7, 2023 was analyzed. Additional tests involving cointegration and Block Exogeneity Wald Tests were integrated to provide a nuanced approach distinct from prior-related examinations. The study shows positive bi-directional safe haven trends between EUR-USD, EUR-GBP and EUR-RUB. Along similar lines, the Euro’s value against the Russian ruble was impacted by 283.356 in a significant positive and cointegrated manner. It was reported that simultaneous negative shocks between EUR-CHF, EUR-GBP and EUR-RUB boost each currency pair’s covariance in the next period. The study further uncovered that negative shocks in either EUR-USD or EUR-CHF exchange markets significantly increase the covariance between the two exchange markets. Accordingly, the study concludes that changes in EUR-USD, EUR-GBP, EUR-CHF and EUR-RUB currency demand during the Russian-Ukraine conflict reflect investors’ safer assets/haven seeking behaviour. Geopolitical events can significantly impact financial markets, and understanding the specific effects on exchange rates is crucial for policymakers, investors, and businesses. The relevancy of financial market regulation, economic policy coordination, monetary policy adjustments, exchange rate stability and capital flows and investment policy implications cannot be overruled in this regard. International cooperation and coordination may be necessary to manage potential systemic risks.